The effects of technology on translation students in academic translation teaching - Odacıoğlu, Mehmet Cem; Korktuk, Saban; Odacıoğlu, Mehmet Cem (ScienceDirect, 2015)
This paper aims at touching upon effects of technological developments on the translation teaching in the 21st century. These technological developments are usually in the area of Information Technology (IT) contributing to the fast growth of the computer industry. The popularization of the computer, especially in the early 1980s changed actually the way translator follows in the translation process through the appearence of useful translator tools including translation memories, terminology databases, translation management programs, electronic corpora and so forth. These breakthroughs happening in the computer technologies also triggered a different perception of what we call functional translation theories defending that every translation is made for a purpose and suggesting a target oriented approach. In the past a translator had to translate using a typewriter or paper and pen. The development of the technology, however, encouraged the translation industry or more appropriately, now localization industry to adopt new tools in the translation process. While explaining all these points, the study follows a descriptive and comparative methodology
Sözlü olarak sunulan bildiri tam metin olarak da yayınlanmıştır.
Keywords: Information technology; Electronic corporas; Terminology database; Translation memory; Translation managament programs; Computer technologies; Functional translation theories; Bilgi teknolojisi; Elektronik şirket; Terminoloji veritabanı; Çeviri belleği; Çeviri yönetimi programları; Bilgisayar teknolojileri; Fonksiyonel çeviri kuramları